Efektivitas Strategi Segmenting, Targeting dan Positioning Produk Tabungan iB Hijrah Haji Pada Bank Muamalat Indonesia - Shinta Julia Nursusilo Wati; Wartoyo Wartoyo; Abdul Ghoni (el-Jizya: Jurnal Ekonomi Islam, 2025)
This study aims to determine how the effectiveness of segmenting, targeting and positioning strategies on iB Hijrah Hajj Savings Products at BMI KC Sumber Cirebon ratio of effectiveness indicators which include product understanding, on time, on target, achieving goals and real changes. This research is a qualitative study with primary data collection and secondary data. Primary data obtained by observation, interviews and documentation. While secondary data is obtained through literature relevant to the research focus. The results of this study indicate that the segmenting strategy used by BMI KC Sumber Cirebon is directed through grouping customers based on criteria in existing customer data grouped by geographic, demographic or psychographic. In the targeting strategy, each segment is based on existing customer data that has Hajj savings products so that the target is in a concentrated market. Positioning prioritizes offering Hajj savings to customers so that it is labeled as “Hajj Bank” in the community. The application of service excellence, feature factors, price and quality of the products offered have a positive impact on the product. In the calculation of effectiveness, it shows that the STP strategy on Hajj savings products at BMI KC Sumber Cirebon is declared very effective with a ratio of 87.33%. Keywords: Effectiveness, segmenting, targeting and positioning strategies and Hajj Savings.